THE STRATEGIC ROLE OF THE 'TEACHER LEADERSHIP' MASTER'S EDUCATIONAL PROGRAM IN THE FRAMEWORK OF THE 'EDUCATION FOR ALL' GLOBAL MOVEMENT (EDUCATION IN THE 21ST CENTURY, 2023)
At all times, the crucial role of teaching staff has been emphasized and valued, not only in ensuring the quality of education, but also in educating a generation and citizen with a comprehensive and harmoniously developed, healthy psychology, state thinking, civic self-awareness and independent activity for the given country and nation, i.e. in building the future of the country. Therefore, the question of the importance of the "Teacher Leadership" educational program, analyzed in the article, is relevant, because it solves both human resources and security issues in the villages of the border regions, based on the right of children to education, with the principle of equal education. The article explains that according to the UN Convention on the Rights of the Child (1989) and the RA Law on the Rights of the Child (1996), every child living in Armenia, regardless of his nationality, race, gender, social status, religion, has equal rights, including the right to education. The article also shows that all children have the right to equal education, regardless of whether they live in the village or in the city. Meanwhile, today we have a different picture in Armenia. We have a great teaching staff shortage in the schools of remote marzes and villages of border regions. There are schools in those villages that do not have teachers for two, three, or even four subjects. And the educational program "Teacher Leadership" is dedicated to the solution of this important issue, which prepares teachers especially for schools in the villages of the border regions and remote marzes of Armenia.The educational program is implemented by the joint efforts of Yerevan State University's Pedagogy and Education Development Center and "Teach for Armenia" Foundation. In 2022, a Cooperation agreement was signed between YSU and the "Teach for Armenia" foundation for the implementation of the project.In the framework of the educational program, along with the courses of the pedagogical educational block, students are given courses that will form leadership abilities in them. The latter will help them carry out leadership activities not only in the school, but also in the community, ensuring school-family-community cooperation.Key words: Teacher leadership, right to education, work-based learning, equal and excellent education, rights of the child, community leadership.
Keywords: Teacher leadership; right to education; work-based learning; equal and excellent education; rights of the child; community leadership